Student's Satisfaction with Research-Based Learning Management in the Course of Literature Theory and Teaching Thai Literature - Khunmathurot, Songphop; Witchayapakorn, Kanchana (Academic and Research Journal of Liberal Arts (Online), 2021)
This research is a research-based learning management, in Literature Theory and Teaching Thai Literature of master's degree students, Department of Thai Language, Faculty of Education, Naresuan University. The objectives were to 1) study the students' satisfaction with the research-based learning management in the Literature Theory and Teaching Thai Literature course; 2) to study the satisfaction with the instructors in the Literature Theory course with teaching Thai literature. The target group is Master's degree students. Department of Thai Language, 2nd year, Faculty of Education, Naresuan University, 21 students enrolled in Literature Theory and Teaching Thai Literature Course, second semester, academic year 2020 and a questionnaire on student satisfaction towards instructors. The statistics used in the analysis were to find the mean ( ) standard deviation (S.D.). The results of the research showed that 1) Master's degree students Department of Thai Language, Faculty of Education, overall satisfaction in the research-based learning management in Literature Theory and Thai Literature Teaching. At the highest level the mean values ​​were ( = 4.60, S.D. = 0.42) and 2) the students were satisfied with the instructors in the Literature Theory course and teaching Thai literature. At the highest level the mean is ( = 4.61, S.D. = 0.49), reflected that the students were satisfied with the learning management by using research as the base of the instructors. This is a method of teaching and learning that is suitable for teaching at the graduate level.